(untitled) - Crane, Beverley E. (Lanham, 2014)
Designed for any librarian who needs to teach either one person at a time or an entire class, this book is a guide to becoming proficient in teaching users how to access, evaluate and use information. Covering both face-to-face and online teaching and learning, the book is divided into three parts: Part 1, Essential Background on Learning & Teaching, gives you just enough background on learning theory, how to plan good instruction, and how to deliver it. Part 2, How to Design, Create, and Deliver Instruction, will help you assess the advantages and disadvantages of each type of instruction and select the best mode for your content. It also illustrates instructional strategies and offers model lesson plans for creating online and face-to-face instruction. Part 3, All About Self-Paced Instruction, highlights ways of using individualized instruction either by itself or as a complement to other teaching. Lesson plans with step-by-step instructions and advice on creating objectives, presenting activities, and evaluating instruction are also included.
Keywords: Information literacy,Kỹ năng thông tin; Study and teaching,Giảng dạy và nghiên cứu